THE INFLUENTIAL IMPACTS OF DIGITAL STORYTELLING TOWARDS THE IMPROVEMENT OF EFL LEARNERS’ SPEAKING SKILLS - Kristian Florensio Wijaya (Universitas Teknokrat Indonesia, 2023)
AbstractIn this ever-changing modern age, EFL educators are still in search of more meaningful speaking learning enterprises by which second language learners are strongly encouraged to endure various L2 communication practice hurdles to transform into more proficient speakers. One of the promising ways to actualize this speaking-learning aspiration is through the use of digital storytelling. Previous researchers believed that digital storytelling could potentially promote a higher degree of speaking learning enjoyment where EFL learners’ speaking competencies can thrive to the utmost potential. This present small-scale library study was initiated to exhaustively investigate the positive influences of digital storytelling on EFL learners’ speaking skills improvement. To release this main study objective, the researcher conducted a thematic analysis of 25 previous digital storytelling and speaking studies to generate more relevant and comprehensible research results. Based on the thematic analysis, the constant utilization of digital storytelling was proved to transform EFL learners into more insightful L2 speakers and promote a psychologically sound speaking learning atmosphere in which their targeted L2 communicative competencies can be fostered to the fullest development. Future researchers need to include broader English language learning scopes and a greater number of reviewed digital storytelling investigations to generate more rewarding research results relevant to the applicability and feasibility of online learning platforms in modern EFL learning enterprises. Keywords: digital storytelling, speaking skills, library study